2019
DOI: 10.7575/aiac.alls.v.10n.3p.145
|View full text |Cite
|
Sign up to set email alerts
|

Structural Organisation of Research Article Titles: A Comparative Study of Titles of Business, Gynaecology and Law

Abstract: Since titles are gateways to the heart of research articles (RAs), their organisational structure should be regarded very crucial in appealing to the potential reader. This study aimed to investigate how titles of RAs are presented in three disciplines (Gynaecology/Obstetrics, Business, and Law). After a thorough study of 574 titles, the study revealed that Business titles were averagely longer than those in the other two disciplines. In terms of title style, it was revealed that the Single Unit Title was exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have identified several areas of interest, including the frequency of word use, the number of authors, the length of titles, and colonicity. Of these, the literature seems ambivalent to the impact of title length and colonicity (Appiah et al, 2019;Lewison & Hartley, 2005).…”
Section: Article Titlesmentioning
confidence: 99%
“…Previous studies have identified several areas of interest, including the frequency of word use, the number of authors, the length of titles, and colonicity. Of these, the literature seems ambivalent to the impact of title length and colonicity (Appiah et al, 2019;Lewison & Hartley, 2005).…”
Section: Article Titlesmentioning
confidence: 99%
“…In a comparative study across disciplines, Appiah et al (2019) analyzed 574 RA titles in the fields of Gynaecology, Business, and Law. It was found that article titles in Business were longer in terms of word count compared to those in Gynaecology and Law.…”
Section: Introductionmentioning
confidence: 99%